2019
DOI: 10.1371/journal.pone.0217897
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of nuclear transport factors and surface-conjugated FG nucleoporins: Insights and limitations

Abstract: Protein-protein interactions are central to biological processes. In vitro methods to examine protein-protein interactions are generally categorized into two classes: in-solution and surface-based methods. Here, using the multivalent interactions between nucleocytoplasmic transport factors and intrinsically disordered FG repeat containing nuclear pore complex proteins as a model system, we examined the utility of three surface-based methods: atomic force microscopy, quartz crystal microb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 82 publications
2
6
0
Order By: Relevance
“…Gold surfaces coated with Nsp1 or Nsp1-S were characterized with SPR under similar coating conditions as for QCM-D, yielding grafting distances of 4.9 ± 0.1 nm for Nsp1 and 5.8 ± 0.4 nm for Nsp1-S. Upon flushing Kap95, we found, consistent with previous studies 27 , 40 , a concentration-dependent adsorption to Nsp1 brushes (Fig. 2e ), whereas we did not observe any detectable interaction between Kap95 and Nsp1-S (Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Gold surfaces coated with Nsp1 or Nsp1-S were characterized with SPR under similar coating conditions as for QCM-D, yielding grafting distances of 4.9 ± 0.1 nm for Nsp1 and 5.8 ± 0.4 nm for Nsp1-S. Upon flushing Kap95, we found, consistent with previous studies 27 , 40 , a concentration-dependent adsorption to Nsp1 brushes (Fig. 2e ), whereas we did not observe any detectable interaction between Kap95 and Nsp1-S (Fig.…”
Section: Resultssupporting
confidence: 89%
“…This minimizes unintentional interactions between Kap95 and gold for subsequent binding experiments (Supplementary Fig. 5 ) 17 , 18 , 40 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Upon binding of Nsp1 and Nsp1-S to the gold surface under the same conditions as for NupX, we measured a '~5 .8 nm and '~5 .4 nm for Nsp1 and Nsp1-S, respectively, gratifyingly close to the value for NupX. Consistent with previous studies 27, 45 , we found that Kap95 exhibits a concentration-dependent absorption to Nsp1 brushes ( Figure 2e), whereas we did not observe any detectable interaction between Kap95 and Nsp1-S ( Figure 2h).…”
Section: Qcm-d Experiments and MD Simulations Show Selective Bindingsupporting
confidence: 90%
“…Assuming 35% of the sensed film to be constituted by protein mass 43 , with the remaining 65% being constituted by coupled water, we estimated an average grafting distance ' between adjacent NupX proteins of '~5 .6 nm, assuming a triangular lattice (since an equilateral triangulated (hexagonal) lattice is the densest type of packing that can be described by a unique length scale that sets the grafting density). After the Nup-layer was formed, a 1-mercapto-11undecylte-tra(ethyleneglycol) molecule, which is expected to form a ~2 nm thin passivating film 17 , was added to passivate any remaining bare gold that was exposed in between NupX molecules, which minimizes unintentional interactions between Kap95 and gold ( Figure S3) 17,18,45 . After thus setting up a NupX-coated layer, we flushed in Kap95 at stepwise increasing concentrations (~10-1000 nM, Figure 2b) and monitored binding to the NupX-coated surface.…”
Section: Qcm-d Experiments and MD Simulations Show Selective Bindingmentioning
confidence: 99%
“…While important insight was obtained from studies in cellular models [ 11 , 12 , 13 , 14 ], much of our understanding about NPC mediated transport comes from in vitro and in silico (physics-based computational) studies assessing the roles of FG Nup assemblies, NTR binding to FG Nups, effects of NTRs on NPC morphology, and the role of cellular environment in effective transport [ 33 , 34 , 35 , 36 , 37 ]. Additionally, in vitro and in silico NPC (barrier) mimics have been powerful tools for interrogating transport, probing interactions between FG Nups and NTRs, and detailing NPC mediated transport [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%